The relevance of the Basel III Accord within the South African banking system - Nkopane, Teboho (My University, 2017)
Title: The relevance of the Basel III Accord within South African Banking. There are numerous countries which are regulated by the Basel II Accord that manifested different results from the 2007 subprime crisis. The United States and some European Countries emanated the subprime crises and experienced massive decline in market confidence as write-offs became the order of the day. The write offs became so severe that the Federal Bank of the United States had to step in to offer massive bailouts to rescue the American banking industry. However, conversely to what happened in America, there some countries (including South Africa) which were also regulated by the Basel II Accord but did not experience massive write-offs as a result of the subprime crisis? This begs a question of whether there is a deeper reason for the failure of the American and European banking system to the extent that they had to bailout their banks during the 2007 financial crisis. With this question remaining unanswered, there remains skepticism on whether a country regulator can rely on implementing the Basel III Accord for improved banking sector resilience. In particular, the stringent requirements of the introduction of liquidity standards will be costly to implement in South Africa. Therefore, a question will need to be asked whether the Basel III Accord is relevant in South Africa.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits School of Governance, 2016.
Keywords: Banks and banking--South Africa; Basel III Accord (2010)